The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/10408440701749421
|View full text |Cite
|
Sign up to set email alerts
|

IPCS Framework for Analyzing the Relevance of a Noncancer Mode of Action for Humans

Abstract: Structured frameworks are extremely useful in promoting transparent, harmonized approaches to the risk assessment of chemicals. One area where this has been particularly successful is in the analysis of modes of action (MOAs) for chemical carcinogens in experimental animals and their relevance to humans. The International Programme on Chemical Safety (IPCS) recently published an updated version of its MOA framework in animals to address human relevance (cancer human relevance framework, or HRF). This work has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
179
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(182 citation statements)
references
References 16 publications
0
179
0
Order By: Relevance
“…For the mode of action analysis and assessment of human relevance, we utilize the framework that has evolved from the initial mode of action document published by International Programme on Chemical Safety (IPCS) and the US EPA, and subsequent publications on the evaluation of the human (Hill 1965)� We rely primarily on the framework presented by Meek et al� (2003) in Critical Reviews in Toxicology, with some additional incorporation of recent suggestions regarding life stages and default assumptions (Boobis et al�, 2006(Boobis et al�, , 2008Seed et al�, 2005)�…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For the mode of action analysis and assessment of human relevance, we utilize the framework that has evolved from the initial mode of action document published by International Programme on Chemical Safety (IPCS) and the US EPA, and subsequent publications on the evaluation of the human (Hill 1965)� We rely primarily on the framework presented by Meek et al� (2003) in Critical Reviews in Toxicology, with some additional incorporation of recent suggestions regarding life stages and default assumptions (Boobis et al�, 2006(Boobis et al�, , 2008Seed et al�, 2005)�…”
Section: Overviewmentioning
confidence: 99%
“…Mode of action (MOA) is increasingly being considered in the risk assessment of pesticides� During the past decade, the International Life Sciences Institute (ILSI) and the International Programme on Chemical Safety (IPCS) of the World Health Organization (WHO) have been evolving a framework for the analysis of mode of action for rodent toxicity and carcinogenicity findings along with assessment of their human relevance (Sonich-Mullin et al�, 2001;Meek et al�, 2003;Seed et al�, 2005;Boobis et al�, 2006Boobis et al�, , 2008� Numerous case studies have been published illustrating the applicability of the framework for genotoxic and nongenotoxic cancer modes of action and for cancer and noncancer endpoints� Mode of action analysis has been incorporated into the risk assessment guidelines of various regulatory agencies, including the US Environmental Protection Agency (US EPA, 2005)� Folpet and captan are used for their fungicidal properties in both industrial and agricultural products� Their structures are shown in Figure 1 along with their reaction with thiols� Both compounds have Reregistration Eligibility Decisions (REDs) issued (US EPA 1999a, 1999b as well as subsequent reviews (US EPA 2003, 2004a, 2004b) that included the reclassification of captan from "B2" (probable human carcinogen) to "not likely" at dietary exposures expected from agricultural use (US EPA, 2004a;Gordon, 2007)� The major tumor finding from captan bioassays was gastrointestinal adenomas and adenocarcinomas in mice, primarily in the duodenum� By contrast, there was no carcinogenic effect of captan in rats� The 2004 cancer reclassification was based on the 1999 proposed Carcinogenic Risk Assessment guidelines (US EPA, 1999c) that were finalized in 2005 (US EPA, 2005)� Folpet, chemically and biologically similar to captan, has also been evaluated in rodent carcinogenicity bioassays and has a similar pattern of tumor development, that is, gastrointestinal tumors in mice and the absence of treatmentrelated tumors in rats� Studies evaluating the early stages of effects in the gastrointestinal tract support analysis of the mode of action� Folpet provides an example of how the application of the ILSI/IPCS mode of action and human relevance framework can be applied to tumors in assessing possible carcinogenic risk to humans� Folpet previously was considered by EPA a genotoxic carcinogen, like captan, and was considered a carcinogen in mice and rats (Quest et al�, 1993)� Given the information available concerning mode of action, assessment of human relevance and the precedent setting case of captan, folpet today would likely be classified as a nongenotoxic, threshold-based carcinogen, with carcinogenicity only in mice� We describe below the basis for concluding that the rat bioassays are negative; this has also been the conclusion of Joint Food and Agriculture Organization of the United Nations (FAO/WHO) Meeting on Pesticide Residues (JMPR) (FAO/WHO, 1996) and European Food Safety Au...…”
Section: Introductionmentioning
confidence: 99%
“…[3] A critical element of this cluster is its focus on repeated dose toxicity and the adoption of a mode-of-action (MOA) framework based on an understanding of key biological events driven by levels of exposure over time. [4][5][6][7][8] The SEURAT-1 cluster is comprised of five complementary research projects (COSMOS, [9,10] DETECTIVE, [11,12] HeMiBio, [13][14] NOTOX, [15][16][17] Abstract: The aim of the SEURAT-1 (Safety Evaluation Ultimately Replacing Animal Testing-1) research cluster, comprised of seven EU FP7 Health projects co-financed by Cosmetics Europe, is to generate a proof-of-concept to show how the latest technologies, systems toxicology and toxicogenomics can be combined to deliver a test replacement for repeated dose systemic toxicity testing on animals. The SEURAT-1 strategy is to adopt a mode-of-action framework to describe repeated dose toxicity, combining in vitro and in silico methods to derive predictions of in vivo toxicity responses.…”
Section: The Seurat-1 Clustermentioning
confidence: 99%
“…These additional MoA data can be useful to support or refute the human relevance of a toxicity fi nding, which may lead to cessation of further development of a new active substance or to further research to elucidate the MoA. The MoA/HRF was developed by the International Programme on Chemical Safety (IPCS) of the World Health Organization (WHO) , 2008, Sonich-Mullin et al 2001) and ILSI , Seed et al 2005, and can be used as a template upon which to elucidate the human relevance of eff ects observed in animals. As the MoA/HRF approach is becoming an accepted component of PPP human health assessment, this paper, along with the companion papers , Ellis-Hutchings et al 2014, LeBaron et al 2014, discusses the application of the MoA/HRF approach to a recently registered active substance, sulfoxafl or.…”
Section: Introductionmentioning
confidence: 99%